Robust bi-level optimization of relief logistics operations - Safaei, Abdul Sattar; Farsad, Saba; Paydar, Mohammad Mahdi (Applied Mathematical Modelling, 2018)
In this paper, a robust bi-Ievel optimization model is developed for a supply-distribution relief network under uncertainty in demand and supply parameters. It optimizes the relief operating costs as well as considering a penalty term for unsatisfied victims' demands. Moreover, the proposed framework optimizes the relief commodity flow in a relief chain along with the supply risk minimization by identifying the suppliers with a lower risk. This paper proposes an integrated optimization method in which the supply risk value for each supplier is obtained via the TOPSIS method. Next, these values are utilized in a robust bi-level model to select appropriate suppliers and allocate orders. Finally, the robustness and effectiveness of the proposed model are demonstrated by a case of flood disaster.